Pola asuh orang tua terhadap kenakalan remaja - Wardania, Siti (Maliki Interdisciplinary Journal, 2024)
One of the factors that contribute to the occurrence of juvenile delinquency is the influence of parents on child development. The wrong way of raising children will encourage them to rebel against their parents, break the rules that have been set, and always deviate. If not handled properly and quickly, the wrongdoings of teenagers will turn into wrongdoings which can lead to acts of violating norms. So, why does the family play an important role? Because the role of the family can prevent juvenile delinquency, and if parents apply appropriate parenting techniques, the child's behavior will be affected. The application of teaching that is in accordance with the development and intelligence of the child will be the key to the good of the child in the future. Good parenting is parenting that is covered with affection and tenderness.